Evaluation of clinical and genetic factors in the population pharmacokinetics of carbamazepine. Issue 6 (14th December 2020) - Yip, Vincent L.M.; Pertinez, Henry; Meng, Xiaoli; Maggs, James L.; Carr, Daniel F.; Park, B. Kevin; Marson, Anthony G.; Pirmohamed, Munir
Abstract : Aims: Carbamazepine can cause hypersensitivity reactions in 10% of patients. An immunogenic effect can be produced by the electrophilic 10, 11‐epoxide metabolite but not by carbamazepine. Hypothetically, certain single nucleotide polymorphisms might increase the formation of immunogenic metabolites, leading ultimately to hypersensitivity reactions. This study explores the role of clinical and genetic factors in the pharmacokinetics (PK) of carbamazepine and 3 metabolites known to be chemically reactive or formed through reactive intermediates. Methods: A combination of rich and sparse PK samples were collected from healthy volunteers and epilepsy patients. All subjects were genotyped for 20 single nucleotide polymorphisms in 11 genes known to be involved in the metabolism or transport of carbamazepine and carbamazepine 10, 11‐epoxide. Nonlinear mixed effects modelling was used to build a population‐PK model. Results: In total, 248 observations were collected from 80 subjects. A 1‐compartment PK model with first‐order absorption and elimination best described the parent carbamazepine data, with a total clearance of 1.96 L/h, central distribution volume of 164 L and absorption rate constant of 0.45 h −1 . Total daily dose and coadministration of phenytoin were significant covariates for total clearance of carbamazepine. EPHX1 ‐416G/G genotype was a significant covariate for the clearance of carbamazepine 10, 11‐epoxide. Conclusion: Our data indicate that carbamazepine clearance was affected by total dose and phenytoin coadministration, but not by genetic factors, while carbamazepine 10, 11‐epoxide clearance was affected by a variant in the microsomal epoxide hydrolase gene. A much larger sample size would be required to fully evaluate the role of genetic variation in carbamazepine pharmacokinetics, and thereby predisposition to carbamazepine hypersensitivity.